Awareness and attitude of female undergraduates of University of Ibadan towards human papilloma virus (HPV) and its vaccine. (2019)
Background: Struma ovarii—an uncommon type of benign germ-cell tumor of the ovary—is mainly composed of thyroid tissue. The presence of ascites has been reported in*20% of all cases, while a combination of struma ovarii and elevated serum levels of cancer antigen (CA)–125 has been rarely reported. Case: A 57-year-old postmenopausal woman presented with a complex pelvic mass associated with ascites and marked elevation of serum CA-125. The clinical impression was ovarian malignancy and she was worked up for staging laparotomy. During surgery, she had total abdominal hysterectomy, bilateral salpingo-oophorectomy, and omentectomy following significant intraoperative findings of 7600mL of straw-colored ascitic fluid and a right ovarian mass (with both cystic and solid components) measuring 10 cm • 12 cm • 12 cm. A final diagnosis of struma ovarii was made histologically. Results: There was an immediate resolution of the ascites and associated normalization of the patient’s serum CA-125 level following surgical excision of the pelvic mass. At a 6-month follow-up, she remained free of ascites or tumor recurrence while her laboratory and clinical parameters have also remained normal. Conclusions: Clinically, struma ovarii can mimic ovarian malignancy, especially when presented as a complex mass with associated ascites and a high serum CA-125 level. This should be considered when evaluating ovarian masses. ( J GYNECOL SURG 35:38)